2022
DOI: 10.3389/fpubh.2022.992773
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of rectal self-sampling in non-clinical venues for chlamydia and gonorrhea testing among men who have sex with men: A cross-sectional study in Shenzhen, China

Abstract: BackgroundRectal Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) infections among men who have sex with men (MSM) have become an increasingly important concern. The study aimed to explore (1) the acceptability of rectal self-sampling for chlamydia and gonorrhea testing among MSM in non-clinical venues in Shenzhen city, China; (2) factors associated with the acceptability of rectal self-sampling; and (3) factors associated with rectal CT and NG infections, respectively.MethodsThis cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Eighty per cent of studies (36 of 45) detected newly diagnosed positive CT/GC infections and 42.2% of studies (19 of 45) measured test accuracy 16 17 20 22–55. Seventeen studies reported 2×2 table values 22 28 30–33 35 36 38–43 51–53.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eighty per cent of studies (36 of 45) detected newly diagnosed positive CT/GC infections and 42.2% of studies (19 of 45) measured test accuracy 16 17 20 22–55. Seventeen studies reported 2×2 table values 22 28 30–33 35 36 38–43 51–53.…”
Section: Resultsmentioning
confidence: 99%
“…Acceptability for SS was high (80.0%–100.0%; n=21) 28 30 32–35 41 42 44–46 49–52 55–60. Participants found SS easy (n=14) and comfortable (ie, painless; n=9), and would recommend it to others (n=3) 28 30 33 35 41 44–46 49 51 52 57–60.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations